USULAN PENGHEMATAN DAYA LAMPU PADA RUANGAN LABORATORIUM KOMPUTASI FAKULTAS TEKNIK DAN RUANGAN SEJENISNYA DI UNIVERSITAS PEMBANGUNAN NASIONAL “VETERAN” JAKARTA - Montreano, Donny; Faradisti, Ghea (Bina Teknika, 2015)
The light in the workspace should be set for a comfortable and healthy employees. If possible energy saving will be even better. In this research, the object of the case study is Computer Laboratory Room in the Faculty of Engineering UPN “Veteran” Jakarta. Problems were found in Computer Laboratory Room is a waste of energy if the lamp position higher than the lamp that hung using a rope. The electricity wastage would be better if it can be minimized, so that the university can take advantage of the budget is wasted on inefficient lighting for research activities and improvement of facilities in the university environment. So that savings can be achieved then the first step is to determine the formulation of the relationship between the intensity of light, lamp power and distance can use Multiple Linear Regression and Poisson regression methods. After processing the data and analysis can be seen equation fluorescent light: Lux Neon = exp (Y '), Y' = 4.248 + 0.04698 Watt Neon - 0.007542 Distance, and spiral lamps equation: Lux Spiral = exp (Y ') , Y '= 3.385 + 0.06330 Watt Spiral - 0.005169 Distance.